Neoplasia mucinosa de baixo grau do apêndice cecal: estudo clínico-patológico em uma série de casos e revisão da literatura - Feitosa, Syone de Jesus (2017)
Aims: The aim of this study is to delineate clinical and histopathological features of mucinous neoplasia of the appendix. Methods: This is a retrospective and descriptive study of mucinous neoplasia of the appendix over a four years period. Cases were selected from a Pathology Laboratory files. Results: 10 cases of low grade mucinous neoplasia were selected (6 females and 4 males). Mean age was 57,3 years, with a range of 30-89 years. Mucocele was detected in 9 cases (90%). Mean size was 8,3 cm, with a range of 3,0-23,0 cm. Acute appendicitis was observed in one case. All cases showed low-grade dysplasia, villiform intraluminal epithelial mucinous proliferation, loss of muscularis mucosae, fibrosis of submucosa and pushing invasion. Calcifications and dissection of acellular mucin in the wall were detected in 09 cases and extra-appendicular acellular mucin in 08 cases. 03 cases disclosed rupture of appendix with free mucus in external surface and in 02 cases Pseudomixoma peritonei was also detected. Concomitant mucinous tumors in ovaries were observed in 02 cases, both with rupture of appendiceal wall. Conclusion: Appendiceal low-grade mucinous neoplasia was mostly detected in females, with a gross picture of mucocele and mucin outside appendix. All cases of Pseudomixoma peritonei showed a ruputure of the appendix wall. Mucinous tumor in ovarires was observed in 02 cases (20%).